Constructing the Character of Deadpool through Swearing Words Exploitation: A Sociolinguistic Analysis of Deadpool 2 Movie - Irawan, Aldho (Universitas Sebelas Maret, 2021)
This study is a qualitative research implementing sociolinguistics approach which aims to gain deeper insights on swearing words exploited in Deadpool 2 movie by the main character of the film. Focusing on the analysis of types and functions of swearing words, the data of this study were taken in the form of utterances produced by Wade Wilson or Deadpool as the main character of the film containing swearing words. Using a conceptual framework of swearing words and their function proposed by Anderson & Trudgill (1990) and classification theory of types of swearing words suggested by Battistellla (2005), the result of the analysis of this study finds out that the use of swearing words by a character in the film as directed by the director provides a unique way to understand the basic characteristic of the character. In the case of this study, Wade Wilson through the analysis of this research, despite having traumatic background and producing more swearing words than any other characters in the film, can be considered somewhat of a good person worthy of the titlle ‘superhero’.lin